A Matlab Tool For The Characterisation of Recorded Underwater Sound (Chorus) - Gavrilov, Alexander; Parsons, Miles (Australian Acoustical Society, 2014)
The advent of low-cost, high-quality underwater sound recording systems has greatly increased the acquisition of large (multi-GB) acoustic datasets that can span from hours to several months in length. The task of scrutinizing such datasets to detect points of interest can be laborious, thus the ability to view large portions of the dataset in a single screen, or apply a level of automation to find or select individual sounds is required. A toolbox that can be continually revised, the user friendly“Characterisation Of Recorded Underwater Sound” (CHORUS) Matlab graphic user interface, was designed for processing such datasets, isolating signals, quantifying calibrated received levels and visually teasing out long and short term variations in the noise spectrum. A function to automatically detect, count and measure particular signals (e.g. blue whale sounds) is integrated in the toolbox, with the ability to include categorised calls of other marine fauna in the future. Sunrise and sunset times can be displayed in long-term average spectrograms of sea noise to reveal diurnal cycles in thevocal activity of marine fauna. A number of example studies are discussed where the toolbox has been used for analysing biological, natural physical and anthropogenic sounds.